Evaluating the Effect of Interleukin-4 in the 3xTg Mouse Model of Alzheimer’s Disease - Dionisio-Santos, Dawling A.; Behrouzi, Adib; Olschowka, John A.; O’Banion, M. Kerry (Frontiers in Neuroscience, 2020)
Chronic neuroinflammation has long been hypothesized to be involved in Alzheimer’s Disease (AD) progression. Previous research suggests that both anti-inflammatory and inflammatory microglia ameliorate amyloid pathology, but the latter worsen tau pathology. In this study, we sought to determine whether induction of arginase-1 positive microglia with the anti-inflammatory cytokine IL-4 modulates pathology in the 3xTg mouse model of AD. Our findings indicate that a single intracranial IL-4 injection positively modulated performance of 3xTg AD mice in a Novel Object Recognition task, and locally increased the levels of arginase-1 positive myeloid cells when assessed one-week post injection. Furthermore, immunohistochemical analysis revealed decreased tau phosphorylation in IL-4 injected animals; however, we were not able to detect significant changes in tau phosphorylation utilizing Western blot. Lastly, IL-4 injection did not appear to cause significant changes in amyloid  load. In conclusion, acute intracranial IL-4 led to some positive benefits in the 3xTg mouse model of AD. Although more work remains, these results support therapeutic strategies aimed at modifying microglial activation states in neurodegenerative diseases.